Annealing of gold nanostructures sputtered on polytetrafluoroethylene - Siegel, Jakub; Krajcar, Robert; Kolská, Zdeňka; Hnatowicz, Vladimír; Svorčík, Václav (Nanoscale research letters, 2011)
Gold nanolayers sputtered on polytetrafluoroethylene (PTFE) surface and their changes induced by post-deposition annealing at 100°C to 300°C are studied. Changes in surface morphology and roughness are examined by atomic force microscopy, electrical sheet resistance by two point technique, zeta potential by electrokinetic analysis and chemical composition by X-ray photoelectron spectroscopy (XPS) in dependence on the gold layer thickness. Transition from discontinuous to continuous gold coverage takes place at the layer thicknesses 10 to 15 nm and this threshold remains practically unchanged after the annealing at the temperatures below 200°C. The annealing at 300°C, however, leads to significant rearrangement of the gold layer and the transition threshold increases to 70 nm. Significant carbon contamination and the presence of oxidized structures on gold-coated samples are observed in XPS spectra. Gold coating leads to a decrease in the sample surface roughness. Annealing at 300°C of pristine PTFE and gold-coated PTFE results in significant increase of the sample surface roughness.